2022
DOI: 10.1007/s40121-022-00694-w
|View full text |Cite
|
Sign up to set email alerts
|

Do ART and Chemsex Drugs Get Along? Potential Drug–Drug Interactions in a Cohort of People Living with HIV Who Engaged in Chemsex: A Retrospective Observational Study

Abstract: Introduction People living with HIV (PLWH) who engaged in chemsex are at risk of potential drug–drug interactions (pDDIs) with recreational drugs. This study aimed to characterize pDDIs between antiretroviral treatment (ART) and chemsex drugs and evaluate their association with unscheduled relevant hospital consultations. Methods We conducted a single-center, retrospective, observational study in a series of gay, bisexual, and other men who have sex with men (gbMSM) liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In a study of 172 HIV-positive chemsex participants, 30% used boosted ART. Of 2048 identified potential drug–drug interactions, 23% were deemed concerning, with 88% due to boosted ART [ 34 ]. Therefore, for the HIV chemsex community, it is crucial to consider non-boosted ART as a safer alternative to minimize potential drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 172 HIV-positive chemsex participants, 30% used boosted ART. Of 2048 identified potential drug–drug interactions, 23% were deemed concerning, with 88% due to boosted ART [ 34 ]. Therefore, for the HIV chemsex community, it is crucial to consider non-boosted ART as a safer alternative to minimize potential drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In other European countries, methamphetamine (Spain), GHB/GBL (Norway, Spain, The Netherlands), and cocaine (Norway, France and Italy) were reported as frequently used drugs in a sexual context ( 16–18 ). Polydrug use is also very prevalent in our study: all participants reported the use of more than one substance, during 95% of all events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to medically prescribed drugs, the use of over-the-counter (OTC) medications and other substances (e.g., vitamins/mineral supplements, anabolic steroids, recreational drugs) is also common among PWH [ 4 , 5 ]. OTC medications may be either victim or perpetrator of DDIs with ARVs, thereby being a potential source for clinically relevant DDIs in PWH.…”
Section: Introductionmentioning
confidence: 99%